Moving beyond differences: A reflection on student intercultural competence - Dalib, Syarizan (2017)
This study aims to consider intercultural competence in the Malaysian setting.Specifically, we examine how the local students of various ethnicities reflect on intercultural competence in their eveyday situations in the campus. Using a qualitative approach, we explore their experiences interacting with the international students and how they move beyond language and cultural differences. We collect data from indepth interviews with selected undergraduate students from thee universities in Northern Malaysia. The findings suggest that intercultural competence constitutes two important themes: language ability and language strategies. The analysis contributes to enriching the emergent literature of intercultural competence that considers students' intercultural experiences in Malaysia.